A mathematical model for predicting the spread and detection of rumors in online communities - Ahlina, Nur; Wahyudi, Agung; Setyawan, Bayu; Sapuguh, Iman; Rosalinda, Adinda Sandra (Institute of Computer Science (IOCS), 2024)
This study investigates the development of a mathematical model to predict the spread and suppression of rumors in online communities. Through mathematical formulation and numerical simulation, the dynamics of rumor spreading are explored by considering factors such as transmission and suppression rates, as well as strategic interventions such as early detection and information intervention. The results show that the model can provide valuable insights into rumor spreading behavior and the effectiveness of control strategies. The findings can support efforts to reduce the negative impact of rumor spreading in online environments and promote healthier and safer online communities.